The Implementation of Flanders Interaction Analysis Category System (FIACS) in an EFL Classroom - Dila Charisma (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2019)
This study focuses on verbal interaction between teacher-students in English classroom. The aims of this study are to find out the type of interaction between teacher-students in MAN 1 Kota Cirebon and to describe the verbal interaction between teacher-students in the classroom. This study employs qualitative research by using descriptive qualitative design. The present study chose the eleventh grade which consist thirty students and one English teacher as the subject. In collecting the data, the present study used observation by using FIACS rubrics and videotaping to identify and analyze teacher and students talk in verbal interaction in English classroom. The data were confirmed by doing the interview with English teacher. The result of this study found, the categories that occur in English classroom, the most significant of the indicators from the teacher talk is Asking Questions. The percentage of the teacher talk is 86,65%, the students talk is 10%, and the silence or confusion is 3,33%. However, the significant of the indicators from the student talk is Student Talk Response. Furthermore, from all FIACS categories, which do not occur in the classroom are Accepts Feelings, Accepts or Uses Ideas of Students, Criticizing or Justifying Authority, and Student Talk Initiation. Verbal interaction in English classroom is considered to be well enough because there were six categories of FIACS that occur in the teaching and learning process that were Praise or Encouragement, Asking Questions, Lecturing/Lecture, Giving Directions, Students Talk Response, Silence or Confusion. Keywords: FIACS; Verbal Interaction; Teacher-Students Interaction; English Classroom.